Instagram Endorsement and Stock Return - Erianto, Bagas Tri; Suryani, Ani Wilujeng (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2023)
Investors obtain information from various sources, including social media, which can make them act irrationally by imitating the decisions of others. This study aims to investigate the impact of influencers endorsements on abnormal stock returns. This event study used 291 Instagram posts by social media influencers. Using Generalized Least Square (GLS), this study demonstrates that endorsement positively affects stock abnormal returns. The endorsement effect appears prior to the post and stops following the endorsement. Endorse was successful in creating a favorable sentiment, so that other investors are interested in making similar decisions to generate abnormal returns. This study shows the short-term effect of endorsements. Therefore, investors need to be aware and make rational decisions.